Al-Qur’an and Modern Geoscience: Part I - Muhammad Zaini; Mulyadi Abdul Wahid; Abd Mujahid Hamdan (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract : Islamic tradition and science have been going through a long history. The Islamic world centred in the Middle East was once a centre of knowledge that was marked by the birth of prominent Islamic scientists and the development of knowledge and technology. Islamic tradition and science are naturally integrated. For instance, it can be seen from the necessity of Earth science knowledge in Islamic ritual practising. However, the decline of Muslim civilization also had an impact on science, including in the field of geoscience. This paper seeks to explain the relationship between the Tafsir al-Qur’an and geoscience, among of them are about the creation of the earth, the structure of the earth, as well as tectonic and volcanism, wherein al-Qur’an they are delivered in many parts.Abstrak : Tradisi Islam dan sains mengalami sejarah yang panjang. Dunia Islam yang berpusat di Timur Tengah pernah menjadi pusat pengetahuan yang ditandai dengan lahirnya ilmuan Islam terkemuka dan pengembangan pengetahuan dan teknologi. Tradisi Islam dan sains terintegrasi secara alamiah termasuk integrasi antara ilmu kebumian dan peribadatan ummat Islam. Namun, kemunduran Islam juga berdampak pada kemunduran di bidang sains, termasuk pada bidang kebumian. Makalah ini berupaya memaparkan hubungan antara tafsir-tafsir Al-Quran dengan ilmu kebumian, diantaranya penciptaan bumi, struktur bumi, serta tetonika dan vulkanisme, dimana hal tersebut telah disebutkan di beberapa bagian di dalam Al-Quran.